Impact of establishing a specialized hepatobiliary unit on liver resections in a non‐specialized tertiary centre in regional Australia. Issue 4 (24th November 2021) - Yeh, John; Palamuthusingam, Pranavan; Cameron, Donald; Avramovic, John
Abstract: Background: In April 2018, a dedicated hepatobiliary unit was established in a tertiary hospital in North Queensland. Changes included the employment of a hepatobiliary‐trained surgeon, centralized referrals, and formalized multidisciplinary team meetings. This study aimed to evaluate the impact of establishing a hepatobiliary unit on outcomes after liver resection, in a regional centre where such procedures were previously performed by non‐specialist general surgeons. Methods: Adult patients who underwent elective liver resection in Townsville from 2013 to 2020 were included in the study. Outcomes after liver resection were collected across two study periods – before and after the hepatobiliary unit was established. The primary end points were a before and after comparison of the 90‐day morbidity and mortality and the R1 margin rates. Results: Across the two study periods, 76 and 77 patients, respectively, underwent liver resection. Rates of R1 resection, 90‐day mortality and major complications were not significantly different between the two study periods. Primary tumours (14.5% before versus 50.6% after) and cirrhosis (1.3% before versus 14.3% after) were significantly higher in the latter period, as was the median length of stay (4 days before versus 6 days after). Annual surgical volume increased by 75% in the period after 2018 compared to the 5 years preceding it. Conclusion: Establishing a centralized hepatobiliary unit in a tertiary regional centre resulted in increased surgical volume and case complexity, with no change in early outcomes after liver resection. Overall, this dedicated unit improved the accessibility of a subspecialty surgical service in regional Australia. Abstract : Outcomes after elective liver resection were compared before and after establishment of a dedicated hepatobiliary unit, in a regional centre where such procedures were previously performed by non‐specialist general surgeons. We found that a centralised, subspecialty unit resulted in increased surgical volume and case complexity, with no change in early outcomes after liver resection. This unit improved the accessibility of a subspecialty service in regional Australia.